After decarbonization - Dwojak, Adam (Instal, 2024)
The article presents the problem of the failure rate of district heating networks, with particular emphasis on preinsulated technology. Nearly 60% of all networks that operate with this modern technology require a change in operating philosophy. The existing methods associated with the diagnosis of duct networks are not reflected in the case of pre-insulated pipelines, a different approach is required. An attempt is made to redefine the concept of heating pipeline failure and to define the rules for the organization of an enterprise focused on security of supply. Using practical examples, the author presents diagnostic methods and determines the usefulness of one of the two surveillance systems used in the Polish district heating industry. In terms of the service life of pre-insulated networks, the problem of operational negligence and the anticipated consequences of such behavior are illustrated in a vivid manner. The advantages and disadvantages of the two surveillance  systems in place are presented, as well as a pessimistic long-term outlook for the non-compliant.
Keywords: pre-insulated heating networks; surveillance system